Top 100 Most-Cited Papers in Neuropathic Pain From 2000 to 2020: A Bibliometric Study - Xiong, Huan-Yu; Liu, Hao; Wang, Xue-Qiang (Frontiers in Neurology, 2021)
Background: Neuropathic pain research has grown impressively in the past two decades, as evidenced by improvements in research quality and increments in the number of research papers. In views of this situation, the use of quantitative measurements to analyze and characterize existing research has become imperative. The aim of this research is to identify and analyze the 100 most-cited papers in neuropathic pain research. Methods: Neuropathic pain-related articles published between 2000 and 2020 were screened from Web of Science (WOS) by using the following subject terms: TI = (Neuralgia OR Neurodynia OR “Neuropathic pain” OR sciatica OR “Nerve pain”). The publications were ranked in a descending order on the basis of citation counts, and the top 100 most-cited neuropathic pain papers were determined. Subsequently, we conducted a bibliometric study to determine the authors, journals, countries, and institutions that contributed the most to the top 100 neuropathic pain lists; describe the keywords and hotspots of the top 100 most-cited papers; and explore the factors associated with successful citations. Results: The top 100 most-cited papers were published from 2000 to 2017, and 2003 had the largest number of published papers (n = 16). The mean number of citations per paper was 480.72, with a range of 262–1,569. Forty-four kinds of journals contributed to the top 100 most-cited papers, which were predominantly published in “Pain” (n = 23). The USA was determined to be the leader of neuropathic pain research in terms of quality and quantity. Conclusion: This study provides a comprehensive list of the most influential papers on neuropathic pain and demonstrates the important advances in this field to help understand academic concerns and the directions of technological innovations in neuropathic pain worldwide.